State Plan Proposals 1979-80 Volume II Government of West Bengal - Planning Commission (Planning Commission, 1978)
The aim of Agricultural and rural development, as statics to document on Draft Five Tear Plan, 1978- 83 published by the Government of India, Planning Commission, will be growth for social justice, achievement of full employment in the rural areas in a % period of 10 years and removal of poverty. The realization of self-sufficiency will continue to be one of the policy objectives. The main thrust of the development policy will be the generation of substantial employment, with a reasonably high level of productivity, Special attention will be paid to the backward areas as well as to the scheduled caste and scheduled tribe families in the rural- areas who are among- the most under VI ledged sections of the population.
Government of West Bengal
Development & Planning Department
Keywords: Land Reforms Department; Animal Husbandry and Veterinary Services Department; Irrigation & Waterways Department; Commerce & Industries Department; Public Undertakings Department; Closed and Sick Industries Department; Youth Services Department; Local Government & Urban Development Department; Information and Cultural Affairs Department; Judicial Department; Finance (Audit) Department